Price Theory and Merger Guidelines - Jaffe, Sonia; Weyl, E. Glen (CPI Antitrust Chronicle, 2011)
Our work extends existing first-order approaches to merger analysis to provide quantitative estimates of price and consumer surplus changes. Sonia Jaffe & E. Glen Weyl (Harvard Univ.)